Advances in the Study of the Mechanisms of Physiological Root Resorption in Deciduous Teeth - Xiao, Manxue; Qian, Hong; Lv, Jingwen; Wang, Peixuan (Frontiers in Pediatrics, 2022)
Physiological root resorption of deciduous teeth is a complex physiological process that is essential for the normal replacement of deciduous teeth and permanent teeth in clinical practice, but its importance is often overlooked due to the presence of permanent teeth. This physiological process includes not only the resorption of hard tissues of deciduous teeth, such as dentin and cementum, but also the elimination of soft tissues, such as pulp and periodontal ligament (PDL). However, the mechanisms of physiological root resorption are not yet clear. In this article, the advances of research on the mechanisms related to physiological root resorption will be reviewed in two main aspects: hard tissues and soft tissues of deciduous teeth, specifically in relation to the effects of inflammatory microenvironment and mechanical stress on the resorption of hard tissues, the repair of hard tissues, and the elimination and the histological events of soft tissues.